2013
DOI: 10.1063/1.4822340
|View full text |Cite
|
Sign up to set email alerts
|

A compact rotating dilution refrigerator

Abstract: We describe the design and performance of a new rotating dilution refrigerator that will primarily be used for investigating the dynamics of quantized vortices in superfluid 4 He. All equipment required to operate the refrigerator and perform experimental measurements is mounted on two synchronously driven, but mechanically decoupled, rotating carousels. The design allows for relative simplicity of operation and maintenance and occupies a minimal amount of space in the laboratory. Only two connections between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Given that these observations are still unexplained, we have used a rigid TO of relatively simple construction mounted on a recently built rotating dilution refrigerator to see if any of these phenomena could be reproduced in another laboratory. The performance of the cryostat was investigated in detail [12] just before the commencement of this experiment. We found that the rotation is smooth to around 1 part in 10 3 and that the amplitude of vibration at the experimental stage below the mixing chamber is ≃ 2 nm at the maximum angular velocity of 2.5 rad s −1 making this an ideal platform to use in a new search for any effect of rotation on solid 4 He.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that these observations are still unexplained, we have used a rigid TO of relatively simple construction mounted on a recently built rotating dilution refrigerator to see if any of these phenomena could be reproduced in another laboratory. The performance of the cryostat was investigated in detail [12] just before the commencement of this experiment. We found that the rotation is smooth to around 1 part in 10 3 and that the amplitude of vibration at the experimental stage below the mixing chamber is ≃ 2 nm at the maximum angular velocity of 2.5 rad s −1 making this an ideal platform to use in a new search for any effect of rotation on solid 4 He.…”
Section: Introductionmentioning
confidence: 99%
“…The darker shading indicates the regions occupied by solid 4 He. The cell was attached to the mixing chamber of a rotating dilution refrigerator[12].3 Measurements at Ω = 0The temperature dependence of the resonant frequency and the inverse quality factor for both the empty TO and when a sample of polycrystalline hcp ∆f max ∆f max color online) Temperature dependence of the TO resonant frequency (top) and inverse quality factor (bottom). In both plots, open symbols show measurements for the empty cell and closed symbols are for measurements with a polycrystalline sample of solid 4 He.…”
mentioning
confidence: 99%